Dry sliding wear in injection molded 17-4 PH stainless steel powder with nickel boride additions - (:unkn) unknown (ELSEVIER SCIENCE SA, 2007)
Dry sliding wear behavior of injection molded 17-4 PH stainless steel powder with nickel boride additions has been studied on a pin-on-disc wear tester using an alloy steel pin and disc of hardness 63 HRC. The PIM alloys in the as sintered as well as in the precipitate-hardened conditions were investigated for their wear behavior. Wear rate was found to be initially decreased with the increasing nickel boride amount. Optical microscopy and XRD analysis were preformed to characterize the basic microstructures for all samples. SEM observations of the worn surfaces revealed plastics deformations with delamination of surface layers by subsurface cracks as the mechanism in the as sintered and precipitate-hardened conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry sliding wear; powder injection molding; sintering; MECHANICAL-PROPERTIES; SINTERED IRON; MICROSTRUCTURE; BEHAVIOR; POROSITY; ALLOYS